Microsite determinants of variability in seedling and cutting establishment in tropical forest restoration plantations. Issue 6 (14th July 2015) - Douterlungne, David; Ferguson, Bruce G.; Siddique, Ilyas; Soto‐Pinto, Lorena; Jímenez‐Ferrer, Guillermo; Gavito, Mayra E.
Abstract Plantations are frequently established on abandoned pasture lands to speed forest recovery. This strategy requires matching a tree species mix with the prevailing microenvironmental conditions. In four degraded pastures of the Mexican Lacandon rainforest, we planted 2, 400 trees of 6 species (Guazuma ulmifolia, Inga vera, Ochroma pyramidale, Trichospermum mexicanum, Bursera simaruba, and Spondias mombin) to (1) test survival, initial growth, and establishment costs; (2) evaluate whether vegetative cuttings outperform direct seeding or transplants of nursery‐raised seedlings; (3) determine tree response to herbaceous dominance and soil compaction; and (4) scrutinize the results' consistency across sites and sampling scales of tree–microenvironment interactions (individual tree vs. averaged plot responses). After 2 years, overall survival and growth rates were high for 2 of 3 nursery‐raised species. Contrary to expectations, all seedlings outperformed the cuttings while direct seeding resulted in a cost‐effective option of intermediate efficacy. The impact of soil resistance to root penetration on tree biomass accumulation was species dependent while bulk density was not relevant. Soil‐covering, herbaceous vegetation accelerated growth in 3 of 4 tested species during the dry season. At this initial stage of forest restoration in abandoned pastures, Guazuma and Trichospermum were the most restoration‐effective species. Costs can be reduced by using direct‐seeding Inga and avoiding weeding during the dry season. Finally, our results demonstrate how species selection trials can be misleading due to site variations in tree response and to sampling scales that fail to account for small‐scale environmental heterogeneity. We recommend ways to improve the design of restoration trials.